Ports and logistics scoping study in CAREC countries.
CAREC members rely on open-sea ports of third-party countries outside borders as conduits for exports and imports. These open-sea ports are located mostly in non-CAREC countries and act as international oceanic trade nodes to connect CAREC freight across cross-border railways, highways, inland sea shipping, and on river and canal barges. The study seeks to identify areas and potential activities that will require cooperation among member countries and development partners within the framework of the CAREC Program.